Zakat Maal Management and Regulation Practices: Evidence from Malaysia, Turki and Indonesia - Mukhlishin, Mukhlishin; Wahab , Abdul; Setiaji, Bambang; Tazhdinov, Magomed (Journal of Human Rights, Culture and Legal System, 2024)
This research investigates the management and regulatory practices of zakat maal (wealth tax) in Malaysia, Turkey, and Indonesia, aiming to provide a comparative analysis grounded in empirical data. Methodologically, the study employs a comparative qualitative analysis based on secondary data from academic literature, government reports, and institutional publications. The results show, first, Malaysia employs a centralized and technologically integrated approach, ensuring transparency and efficiency in zakat collection and distribution. In contrast, Turkey adopts a decentralized model driven by non-governmental organizations and community participation, fostering flexibility but posing challenges in standardization and oversight. Indonesia's hybrid model combines governmental oversight with private sector involvement, aiming to balance regulatory control with local adaptability, yet needs help in coordination and public trust. Second, the policy enhancements such as improved coordination mechanisms, strengthened regulatory frameworks, and enhanced public awareness to optimize Zakat's role in poverty alleviation and social welfare across Malaysia, Turkey, and Indonesia. This research contributes to the broader discourse on Islamic finance and social policy by providing nuanced insights into zakat management practices, offering valuable implications for policymakers, practitioners, and scholars interested in enhancing zakat efficacy globally.